Neuroinflammation in Parkinson’s disease: A study with [11C]PBR28 PET and cerebrospinal fluid markers - Al-Abdulrasul, H.; Ajalin, R.; Tuisku, J.; Zetterberg, H.; Blennow, K.; Vahlberg, T.; Ekblad, L.; Helin, S.; Forsback, S.; Rinne, J.O.; Brück, A. (Parkinsonism & related disorders, 2025)
To investigate neuroinflammation in Parkinson's disease (PD) with [11C]PBR28 positron emission tomography (PET) and cerebrospinal fluid (CSF) biomarkers, and the relationship to dopaminergic functioning measured with 6-[18F]-fluoro-L-dopa ([18F]FDOPA) PET. The clinical cohort consisted of 20 subjects with PD and 51 healthy controls (HC). All HC and 15 PD participants underwent [11C]PBR28 High Resolution Research Tomograph (HRRT) PET for the quantitative assessment of cerebral binding to the translocator protein (TSPO), a neuroinflammation marker. CSF samples were available from 17 subjects with PD and 21 HC and were examined for soluble triggering receptor expressed on myeloid cells 2 (sTREM2), chitinase 3-like 1 protein (YKL-40), neurogranin (NG), alpha-synuclein (aSyn) and oligo-alpha-synuclein. All subjects with PD underwent [18F]FDOPA HRRT PET. While the subjects with PD and HC did not differ in the total volume of distribution (VT) of [11C]PBR28 in any studied brain regions, higher levels of neuroinflammation and neurodegeneration CSF biomarkers sTREM2 and NG, respectively were associated with more severe motor symptoms evaluated by The Unified Parkinson's Disease Rating Scale motor part (UPDRS-III) (r = 0.52, p = 0.041 and r = 0.59, p = 0.016 respectively). Additionally, in the PD group increased [11C]PBR28 VT in the basal ganglia and substantia nigra (SN) was related to higher levels of neuroinflammation biomarker YKL-40 (p < 0.01). Associations between CSF biomarkers, motor disability and [11C]PBR28 VT in the striatum and SN may support a role for neuroinflammation in PD. •Higher sTREM2 and NG levels were associated with increased motor disability in PD.•Higher YKL-40 was associated with higher [11C]PBR28 VT in striatum in PD subjects.•Regional [11C]PBR28 VT did not differ between PD subjects and healthy controls.